2020
DOI: 10.1177/1049732319900498
|View full text |Cite
|
Sign up to set email alerts
|

“Thrown Into the Deep End”: Mapping the Experiences of Young People Living in a Family Affected by a Neurological Condition

Abstract: In this case study research, we investigated the impact that having a parent with a neurological condition can have on young adults’ experiences of growing up and the nature of their support networks. The work was informed by models of interface of chronic conditions and the family. Stroke ( n = 6), multiple sclerosis ( n = 14), and dementia ( n = 11) were selected as discrete cases. Within each case, the researcher (a) carried out semi-structured interviews with young adults (16–25 years) living in families a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Carers reported being excluded from a care ecosystem organized around the health care provider and the person with MS. Partners, 26 carers of persons transitioning to secondary progressive MS and 34 parents of children with MS, especially while in pursuit of a diagnosis, 55,56,61 reported feeling ignored and undervalued by clinicians who did not treat them as equal partners in the health care relationship. Young carers of a parent with MS noted, in particular, that they were marginalized by clinicians whose focus was solely on the parent 27,28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Carers reported being excluded from a care ecosystem organized around the health care provider and the person with MS. Partners, 26 carers of persons transitioning to secondary progressive MS and 34 parents of children with MS, especially while in pursuit of a diagnosis, 55,56,61 reported feeling ignored and undervalued by clinicians who did not treat them as equal partners in the health care relationship. Young carers of a parent with MS noted, in particular, that they were marginalized by clinicians whose focus was solely on the parent 27,28 …”
Section: Resultsmentioning
confidence: 99%
“…This existential uncertainty was psychologically distressing for partners who described not knowing how to help the person with MS 66 and for carers worried about being unable to care for them if they themselves were unwell 27,36,42,46 . Faced with an uncertain future, participants in many studies reported experiencing anxiety and depression, 31,36,41,58,63,65,66 including children 27,28,30,54,60 . The MS diagnosis was overwhelming and worrying for children, and often continued into adulthood 27,60 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to a dedicated team could reduce the level of navigation work imposed on patients and families and could also provide support to practitioners who are less comfortable diagnosing younger patients. Finally, the social, psychological, and financial challenges participants experienced provide further evidence of the need for family-centered supports during the diagnostic process and after (Masterson-Algar & Williams, 2020;Rabanal et al, 2018).…”
Section: Discussionmentioning
confidence: 96%